Primary care physicians’ perceptions of barriers and facilitators to management of chronic kidney disease: A mixed methods study - Sperati, C. John; Soman, Sandeep; Agrawal, Varun; Liu, Yang; Abdel-Kader, Khaled; Diamantidis, Clarissa J.; Estrella, Michelle M.; Cavanaugh, Kerri; Plantinga, Laura; Schell, Jane; Simon, James; Vassalotti, Joseph A.; et al. (PloS one, 2019)
Given the high prevalence of chronic kidney disease (CKD), primary care physicians (PCPs) frequently manage early stage CKD. Nonetheless, there are challenges in providing optimal CKD care in the primary care setting. This study sought to understand PCPs' perceptions of barriers and facilitators to the optimal management of CKD. Mixed methods study. Community-based PCPs in four US cities: Baltimore, MD; St. Louis, MO; Raleigh, NC and San Francisco, CA. We used a self-administered questionnaire and conducted 4 focus groups of PCPs (n = 8 PCPs/focus group) in each city to identify key barriers and facilitators to management of patients with CKD in primary care. We conducted descriptive analyses of the survey data. Major themes were identified from audio-recorded interviews that were transcribed and coded by the research team. Of 32 participating PCPs, 31 (97%) had been in practice for >10 years, and 29 (91%) practiced in a non-academic setting. PCPs identified multiple barriers to managing CKD in primary care including at the level of the patient (e.g., low awareness of CKD, poor adherence to treatment recommendations), the provider (e.g., staying current with CKD guidelines), and the health care system (e.g., inflexible electronic medical record, limited time and resources). PCPs desired electronic prompts and lab decision support, concise guidelines, and healthcare financing reform to improve CKD care. PCPs face substantial but modifiable barriers in providing care to patients with CKD. Interventions that address these barriers and promote facilitative tools may improve PCPs' effectiveness and capacity to care for patients with CKD.